Distribution of Oikopleura Dioica (Tunicata, Appendicularia) associated with a coastal frontal system (39°- 41°s) of the SW Atlantic ocean in the spawning area of Engraulis Anchoita anchovy - Spinelli, Mariela Lorena (2013)
Among tunicates, the small planktonic appendicularians generally comprise a significant fraction of the mesozooplankton in frontal systems. The summer 2011 distribution (vertical and spatial) of Oikopleura dioica was studied in terms of abundance, biomass, estimation of egg production and population structure in the different sectors of the El Rincón coastal front, in the light of thermal and salinity gradients. Peaks of abundance of Engraulis anchoita larvae were compared to O. dioica patterns. Samples were collected with plankton nets of 67 µm and 200 µm at two layers, below and above the thermocline depth. CTD data profiles were also recorded. During this campaign high salinity waters were predominant in the estuarine area. Conversely, a thermal stratification was found, being more marked at the external stations of the front where the highest densities and biomass of O. dioica coincided with the highest E. anchoita larvae densities. The size structure of O. dioica was also associated with the thermal gradient. The smaller sizes were found in the homogeneous area at the coast where the temperature was higher around 22ºC. This front constitutes a suitable environment for O. dioica reproduction enhancing the survival rate and growth of several small pelagic fishes such as E. anchoita.